Perceptions and Participation: Examining Student Engagement in the Implementation of the Merdeka Belajar–Kampus Merdeka (MBKM) Internship Policy in Makassar - Basir, Sutrisman; Misbahuddin, Misbahuddin; Khan, Aditya Sulthony Ahmad; Amalya, Andi Adhe; Madjid, Khadijah (Universitas Pattimura, 2026)
This study examines the extent to which student perceptions shape their participation in the implementation of the Merdeka Belajar–Kampus Merdeka (MBKM) internship policy in Makassar, a national higher education reform designed to strengthen work readiness through experiential learning. The research aims to assess the relationship between students’ perceptions of policy content, information access, institutional support, and resource availability and their engagement in MBKM internship activities, while also identifying the most influential perceptual factors. Employing a quantitative correlational design, the study involved active university students who had participated in at least one MBKM program, using two instruments: a four-dimensional perception scale derived from policy implementation theory and the Student Engagement Measure covering behavioral, emotional, and cognitive dimensions. Pearson correlation analysis reveals a positive and statistically significant association between student perceptions and engagement (p = 0.038), although the weak correlation indicates that perception contributes to but does not fully determine participation. These findings suggest that institutional readiness, motivation, accessibility, and prior experience also shape student involvement. The novelty of this study lies in its socio-political lens on MBKM implementation, its empirical linkage between policy perception and engagement, and its integration of policy implementation and student engagement theories. The study contributes to higher education governance and experiential-learning scholarship by demonstrating that policy reception among students is essential for reform effectiveness.